1963
DOI: 10.1139/v63-261
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Decomposition of Peracetic Acid in the Vapor Phase

Abstract: The thermal decompositioil of peracetic acid i11 a stream of toluene was studied over the temperature range 127-360" C . The main products of the reaction were C02, CHpCOOH, C2H8, C H I , H C H O , 0 2 , and traces of CO. Dibenzyl was also formed.The overall decomposition of peracetic acid was partly heterogeneous and was represented by the two parallel primary reactions(ii)The dissociation energy of the 0-0 bond in peracetic acid was estimated to be 30-34 kcal/mole. I N T R O D U C T I O NThe importance of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It was noted that in the PFA reactor fitted with a back pressure regulator large amounts of gas generated in a process would be trapped inside the reaction mixture, but could otherwise easily escape in a batch scenario with headspace. The literature also confirmed that peracetic acid can spontaneously decompose, generating oxygen 23 that might over-oxidize the reaction intermediates leading to increased amounts of benzoic acid. A test reaction conducted in a closed vessel (port connector) 24 with a limited amount of the overhead space supported this hypothesis as evidenced by an improved nitroalkane yield relative to the regular metal PFR.…”
Section: Resultsmentioning
confidence: 85%
“…It was noted that in the PFA reactor fitted with a back pressure regulator large amounts of gas generated in a process would be trapped inside the reaction mixture, but could otherwise easily escape in a batch scenario with headspace. The literature also confirmed that peracetic acid can spontaneously decompose, generating oxygen 23 that might over-oxidize the reaction intermediates leading to increased amounts of benzoic acid. A test reaction conducted in a closed vessel (port connector) 24 with a limited amount of the overhead space supported this hypothesis as evidenced by an improved nitroalkane yield relative to the regular metal PFR.…”
Section: Resultsmentioning
confidence: 85%
“…Peroxyacetic acid is known to be a potentially dangerous and explosive substance. 39,53 It can be generated by the reaction of hydrogen peroxide with acetic acid. The process is described by the following reaction scheme:…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Peroxyacetic acid is known to be a potentially dangerous and explosive substance. , It can be generated by the reaction of hydrogen peroxide with acetic acid. The process is described by the following reaction scheme: CH 3 normalC ( O ) OH + normalH 2 normalO 2 CH 3 normalC ( O ) OOH + normalH 2 normalO Both the forward and reverse reactions are fairly slow at room temperature, and a long time is necessary for equilibrium to be established .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The RO x (= OH + HO 2 + RO 2 ) radicals and the nitrogen oxides (NO x = NO + NO 2 ) are important trace constituents of the atmosphere that drive diverse processes such as the photochemical production of ozone (O 3 ) in the troposphere (Kirchner and Stockwell, 1996;Fleming et al, 2006), the catalytic destruction of O 3 in the stratosphere (Bates and Nicolet, 1950;Stenke and Grewe, 2005;Solomon, 1999;Portmann et al, 1999), and the chemistry of organic aerosol formation (Ziemann and Atkinson, 2012;Ehn et al, 2014;Crounse et al, 2013). In the troposphere, the concentrations of these species are frequently buffered by RO x and NO x reservoir species, of which peroxynitric acid (PNA, HO 2 NO 2 ), alkyl peroxy nitrates such as methyl peroxynitrate (CH 3 O 2 NO 2 , MPN), and peroxyacyl nitrates (PANs, RC(O)O 2 NO 2 ) are important examples (Singh et al, 1992;Roberts, 1990). Much insight into RO x and NO x chemistry has been gained by measuring the atmospheric abundances of these reservoirs.…”
Section: Introductionmentioning
confidence: 99%